Resolving the Challenges of German Reunification: From the Fall of The Berlin Wall to Systemic Integration - Turakulov Bekzod Turakulovich; Abdurakhmonova Sevinch Zavqi qizi (Next Scientists International Journal JSSHRF, 2026)
This article examines the process of German reunification in 1990, analyzing the major economic, political, and social challenges that arose during this transformation. Having developed under distinct political and economic systems for decades, the two German states exhibited significant disparities in living standards, labor markets, industrial capacity, and infrastructure. The study investigates the reforms and programs implemented by the German government to overcome these challenges, focusing on the modernization of the East German economy, the attraction of investment, the reduction of unemployment, and the strengthening of social protection. Additionally, the article evaluates the long-term outcomes of reunification and its impact on Germany’s overall development. The findings demonstrate that the German experience provides valuable lessons for understanding processes of national integration and the reduction of regional inequalities.